“Implementación del divorcio incausado en la legislación ecuatoriana: Respeto a la intimidad y el libre desarrollo de la personalidad de los cónyuges”. - Cango Salinas, Andrea Karolina (2025)
The current research analyzes the implementation of uncontested divorce in Ecuadorian legislation, focusing on its impact on respect for privacy and the free development of the personality of the spouses. Therefore, based on a normative and jurisprudential analysis, this study seeks to identify the challenges that arise when terminating the marriage bond. No-fault divorce in Ecuadorian legislation represents a significant legal advance, because it promotes the full exercise of fundamental rights that are enshrined in the Constitution of the Republic of Ecuador (2008), such as the free development of personality, with no limitations other than the rights of others, which is established in Article 66, paragraph 5, and the right to personal and family privacy, which is found in the same Article 66, paragraph 20. Thus, the implementation of no-fault divorce in Ecuador will bring significant benefits to spouses, so that they can dissolve the marriage bond without having to allege a cause, thus promoting a more respectful and harmonious environment. Furthermore, the implementation of this type of divorce responds to the needs and constant evolution of society, constituting a milestone in family law. This figure has proven its effectiveness in countries such as Argentina, Mexico and Spain, where significant reforms have been carried out aimed at guaranteeing a more agile, autonomous and less damaging process of marital dissolution for the parties involved. It is worth noting that the adoption of no-fault divorce not only offers important advantages, but also represents a profound transformation in family law, aligning itself with the regulatory trends of other jurisdictions that have already implemented it. This type of divorce not only has significant advantages, but will mark a evolution in family law in Ecuador.